Synthesis, Characterization and Biological Activity of Copper(II) Complexes with Phenylglyoxal bis(Thiosemicarbazones) - Murthy, Narashima; Dharmarajan, T.S. (Asian Journal of Chemistry, 2010)
Six Cu(II) coordination compounds with a novel ligand 4-substituted phenylglyoxal bis (thiosemicarbazones) have been synthesized and characterized by various physico-chemical methods including elemental analysis, UV-visible and IR spectral studies. These compounds were tested for cytotoxic acivity against Ehrlich ascites carcinoma (EAC) cells. In these experiments compounds have demonstrated cell growth inhibition activity. Compounds 1, 2, 3 and 4 have been screened for antimicrobial activity on B. subtilis and E. coli. They inhibited the bacterial growth considerably.